LOYALITAS, MOTIVASI, DAN LINGKUNGAN KERJA SEBAGAI PENENTU KINERJA KARYAWAN PADA RESTORAN BETARI SEAFOOD KEDONGANAN - Anak Agung Ngurah Gede Suindrawan; Anak Agung Bagus Wirateja; I Komang Ogi Sudarmawan (Journal of Tourism and Interdiciplinary Studies, 2021)
This research aims to analyze the effect of loyalty, motivation and work environment as a determinant factor of employees’ performance in Restaurant of Betari Seafood Kedonganan. The type of data being used in this research is quantitative data and collected by distributing questionnaire to 32 respondents. Meanwhile data analysis techniques being used were: instrument test, classic assumption test, multiple linear regression, and hypothesis test partially. The result of research shows the equation of multiple linear regression of Y= - 12.412 + 0.260 X1 + 0.633 X2 + 0.450 X3, it means that loyalty variable has positive value that is 0.260 with t-count score > t-table (2.298 > 1.70113) and has significance value of 0.029 < 0.05 so that it can be concluded that loyalty variable has significant positive effect towards employees’ performance. Motivation variable has positive value that is 0.633 with t-count score > t-table (3.480 > 1.70113) and has significance value of 0.002 < 0.05 so that it can be concluded that motivation variable has significant positive effect towards employees’ performance. Work environment variable has positive value of 0.450 with t-count score > t-table (2.319 > 1.70113) and has significance value of 0.028 < 0.05 so that it can be concluded that work environment variable has significant positive effect towards employees’ performance.